5PSeq analysis conecting translation elongation and protein folding at the ribosome exit tunnel in Saccharomyces cerevisiae - Pelechano, Vicent; Alekseenko, Alisa (Karolinska Institutet, 2021)
Supplementary information for the manuscript: A functional connection between translation elongation and protein folding at the ribosome exit tunnel in Saccharomyces cerevisiae. Olga Rodríguez-Galán, Juan J García-Gómez, Iván V Rosado, Wu Wei, Alfonso Méndez-Godoy, Benjamin Pillet, Alisa Alekseenko, Lars M Steinmetz, Vicent Pelechano, Dieter Kressler, Jesús de la Cruz, Nucleic Acids Research, , gkaa1200, https://doi.org/10.1093/nar/gkaa1200


Here we provide browsable metagene analysis for 5´P mRNA degradation profiles.Raw and processed sequencing data are deposited at Gene Expression Omnibus (GEO) with accession numbers GSE114899. Data was analyzed using fivepseq pipeline http://pelechanolab.com/software/fivepseq/

Related manuscript abstract:

Proteostasis needs to be tightly controlled to meet the cellular demand for correctly de novo folded proteins and to avoid protein aggregation. While a coupling between translation rate and co-translational folding, likely involving an interplay between the ribosome and its associated chaperones, clearly appears to exist, the underlying mechanisms and the contribution of ribosomal proteins remain to be explored. The ribosomal protein uL3 contains a long internal loop whose tip region is in close proximity to the ribosomal peptidyl transferase center. Intriguingly, the rpl3[W255C] allele, in which the residue making the closest contact to this catalytic site is mutated, affects diverse aspects of ribosome biogenesis and function. Here, we have uncovered, by performing a synthetic lethal screen with this allele, an unexpected link between translation and the folding of nascent proteins by the ribosome-associated Ssb-RAC chaperone system. Our results reveal that uL3 and Ssb-RAC cooperate to prevent 80S ribosomes from piling up within the 5’ region of mRNAs early on during translation elongation. Together, our study provides compelling in vivo evidence for a functional connection between peptide bond formation at the peptidyl transferase center and chaperone-assisted de novo folding of nascent polypeptides at the solvent-side of the peptide exit tunnel.


Raw data:Raw and processed sequencing data are deposited at Gene Expression Omnibus (GEO) with accession number GSE114899 and GSE151632
Keywords: Gene expression (incl. microarray and other genome-wide approaches); Microbial genetics; Medical and Health Sciences; Medicin och hälsovetenskap; Genetics and Genomics; Genetik och genomik